Stretchable Oxide TFT for Wearable Electronics. Issue 4 (1st July 2017) - Li, Xiuling; Jang, Jin
Abstract : Oxide thin‐film transistors (TFTs) in a neutral plane are shown to be robust under mechanical bending and thus can also be suitable for TFT backplanes for stretchable electronics. The oxide TFTs when built on a PI substrate can then be transferred onto a PDMS substrate and applied to stretchable electronics. The PDMS regions on the TFT parts are UV/O3 treated for stiff PDMS and then the TFTs are transferred onto this region. This substrate with TFTs applied can then be stretched up to 50 percent without significant performance degradation. Therefore, stretchable oxide TFT arrays can be used for stretchable displays and sensors.